2002
DOI: 10.1016/s0248-4900(02)01189-9
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix development during differentiation into adipocytes with a unique increase in type V and VI collagen

Abstract: In order to study how adipose conversion affects the extracellular environment, levels of extracellular matrix (ECM) proteins during differentiation were analyzed by 125I-labeled antibody binding to each specific primary antibody. When confluent bovine intramuscular preadipocytes (BIP) were stimulated with adipogenic medium, there was a significant accretion on the cell surface of type I-VI collagens, laminin and fibronectin, compared with undifferentiated cells. The deposition amount of ECM proteins had reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 28 publications
(26 reference statements)
3
81
0
Order By: Relevance
“…These newly accumulated extracellular matrix (ECM) macromolecules are comprised of various numbers of collagens, structural glycoproteins and proteoglycans. As previously reported in both mouse and bovine adipocytes (Kubo et al 2000, Nakajima et al 2002a, we also observed the same phenomenon with porcine adipocytes in which a prominent fibrillar network of collagens developed only in differentiated cells, thus forming fat cell clusters (unpublished data). In addition, impairing these ECM networks by treatment of ethyl-3,4-dihydroxybenzoate, a specific inhibitor of collagen synthesis, reduced the level of adipogenesis in mice and bovine (Ibrahimi et al 1992, Nakajima et al 2002b, as well as pig adipocytes (unpublished data).…”
Section: Extracellular Changes During Adipose Conversionsupporting
confidence: 89%
“…These newly accumulated extracellular matrix (ECM) macromolecules are comprised of various numbers of collagens, structural glycoproteins and proteoglycans. As previously reported in both mouse and bovine adipocytes (Kubo et al 2000, Nakajima et al 2002a, we also observed the same phenomenon with porcine adipocytes in which a prominent fibrillar network of collagens developed only in differentiated cells, thus forming fat cell clusters (unpublished data). In addition, impairing these ECM networks by treatment of ethyl-3,4-dihydroxybenzoate, a specific inhibitor of collagen synthesis, reduced the level of adipogenesis in mice and bovine (Ibrahimi et al 1992, Nakajima et al 2002b, as well as pig adipocytes (unpublished data).…”
Section: Extracellular Changes During Adipose Conversionsupporting
confidence: 89%
“…Collagen VI is an ideal candidate due to its relatively abundant and highly enriched expression in adipose tissue. It is the most highly expressed collagen in differentiated adipocytes and undergoes dramatic structural changes during adipogenesis (38). Collagen VI fibrils alter their appearance during differentiation of 3T3-L1 preadipocytes, switching from a thin fibril texture at day 4 of differentiation to a very thick appearance in fully differentiated adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of these and other keratins in this study may affect adipocyte cell shape. Extracellular matrix (ECM) components, such as collagen types I, III, IV, V and VI, increase three-to sixfold under adipogenic conditions (Nakajima et al 2002). Moreover, MMP-2 is also involved in adipocyte development, since it regulates the balance between ECM deposition and degradation.…”
Section: Discussionmentioning
confidence: 99%